2021
DOI: 10.3389/fvets.2021.636809
|View full text |Cite
|
Sign up to set email alerts
|

Eimeria acervulina Microneme Protein 3 Inhibits Apoptosis of the Chicken Duodenal Epithelial Cell by Targeting the Casitas B-Lineage Lymphoma Protein

Abstract: Eimeria acervulina (E. acervulina) causes coccidiosis in poultry which persists as economic pain worldwide. Most damage to the intestinal mucosa results from apoptosis of the infected intestinal epithelial cells. The Microneme protein 3 (MIC3) protein is a key virulence factor in some parasites involved in host cell apoptosis inhibition. Here, we studied whether and how MIC3 affects the apoptosis in E. acervulina infected chicken duodenal epithelial cells. Through flow cytometry (FCM), we found that the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…E. maxima and E. acervulina are species causing malabsorption, also widely studied since they are found with high frequency in the field. In this sense, several immunogenic antigens have been studied in these two species: lactate dehydrogenase [ 121 ], MIF [ 87 ], cSZ-JN1 [ 122 ], cSZ2 [ 122 ], EaMIC3 [ 74 ], EaMIC5 [ 75 ] in addition to EaMIC2, 3-1E, and SAG1 [ 77 ] ( Table 1 ). In the case of E. mitis , only one immunogenic protein, EmiMIC3, has been characterised so far [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…E. maxima and E. acervulina are species causing malabsorption, also widely studied since they are found with high frequency in the field. In this sense, several immunogenic antigens have been studied in these two species: lactate dehydrogenase [ 121 ], MIF [ 87 ], cSZ-JN1 [ 122 ], cSZ2 [ 122 ], EaMIC3 [ 74 ], EaMIC5 [ 75 ] in addition to EaMIC2, 3-1E, and SAG1 [ 77 ] ( Table 1 ). In the case of E. mitis , only one immunogenic protein, EmiMIC3, has been characterised so far [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few mic genes of E. acervulina (EaMIC2, EaMIC3, identified and their function has been investigated. EaM vival since it inhibited cell apoptosis [74]. They all we sporozoites, but EaMIC2 and EaMIC5 are located diffu was suggested that MICs might be translocated to the in contact with the host cell [75].…”
Section: Eimeria Acervulinamentioning
confidence: 99%
See 2 more Smart Citations
“…Altered apoptosis and proliferation rates are frequently seen in disease conditions affecting the avian digestive tract [ 25 , 26 ]. Thus, mapping the normal distribution of apoptotic and/or proliferative cells within the avian digestive tract is a prerequisite for the proper diagnosis and treatment of such diseases [ 27 ].…”
Section: Introductionmentioning
confidence: 99%